Nitrate analysis of Sungai Ulung in Cameron Highlands, Malaysia / Nurfahimah Atikah Rahim .. [et al.] - Rahim, Nurfahimah Atikah; Masngut, Mohd Izwan; Mohamad Shaifuddin, Siti Norashikin; Nasruddin, Hairul Nazmin; Megat Mokhtar, Megat Azman; Mohd Sabri, Muhammad Aflah (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
Excessive fertiliser application in agricultural activities, can be washed into the streams and decline the water quality. Nitrate from fertiliser may increase the oxidising activity especially chemical oxygen demand (COD) and also affect the quality of the river. This research aims to determine the relationship between nitrate concentration with COD, Ammoniacal Nitrogen (AN), temperature, Dissolved Oxygen (DO) and pH of a stream flows within the vegetable farm area. This study used a cross-sectional study design and water samples were collected at seven sampling points of Sungai Ulung in Cameron Highland, Malaysia. The concentration for nitrate, AN and COD at downstream was higher than those in the upstream. The results indicated a positive correlation, where an increase in nitrate concentration corresponded with an increase in COD (r = 0.865*, p = 0.012), AN (r = 0.753, p = 0.051), and temperature (r = 0.847*, p = 0.016), which can be attributed to the oxygendependent decomposition process. Conversely, there were negative correlations, as an increase in nitrate concentration was inversely related to DO (r = -0.775, p = 0.041) and pH value (r = -0.126, p = 0.788), likely due to the reduction of oxygen in water during nitrate decomposition. The degradation river quality of Sungai Ulung was probably due to the agricultural activity near the river. Farmers can practice Best Management Practices (BMPs) for their crop to reduce the chance of nutrient losses to the impaired water bodies.